The Influence of Business Location and Service Quality on Consumer Loyalty with Consumer Satisfaction as a Mediating Variable at PT Giri Aneka Usaha (Perseroda) Giri Husada Wonogiri Pharmacy Unit - Rina Ika Sapitri; Syahri Alhusin; Zandra Dwanita Widodo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The objective of this research is to: 1) test and measure the impact of service quality and business location on customer satisfaction. 2) test and mitigate the effect of quality of service and business site on consumer loyalty. The research was carried out at the Aneka Usaha (Perseroda) Pharmaceutical Unit at Husada district of Wonogiri. The population in this study is the entire customer of Pharmacy Giri Husada. Given the unknown distribution of the population, according to Cooper and Schindler the number of samples taken was 96 rounded to 100 respondents. Research finds that there is an influence on the quality of service and the location of the business on consumer satisfaction. The quality of the service and the location of the business influence the loyalty of the consumer. Consumer satisfaction mediates the quality of the customer service against the loyalty of the consumer, but consumer satisfaction does not mediate the quality of service against the customer loyalty.